Development of a local history module about the cultuurstelsel period based on an inclusive approach for high school students - Rohana, Melda Amelia; Abrar, Abrar; Fakhruddin, M. (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
In the Merdeka curriculum, local history is one of the essential materials. One of the most critical periods in local history in Malang is the cultuurstelsel period, but currently, there are no teaching materials about this period. HIMO is a printed local history module about the cultuurstelsel period with media integration that allows students to various conditions (regular and inclusive). This study aimed to measure the effectiveness of HIMO in improving local history understanding and learning motivation. This research method is R&D using the ADDIE model. In the analysis stage, the researcher analyzed student needs and the curriculum, which was continued with the design stage. In the development stage, HIMO was declared very feasible by material experts (average score of 98%) and teaching materials experts (average score of 89%) with several revisions. Furthermore, the implementation stage was carried out in an inclusive school in Malang (101 students as subjects) with research instruments in the form of comprehension tests and learning motivation questionnaires. Based on the implementation results, it was found that HIMO can improve understanding (94% of students) and learning motivation (average score 77%). Based on these results, at the evaluation stage, HIMO was declared suitable as local history teaching material for inclusive schools.